Chilling requirement evaluation of the Abjosh cultivar (Vitis vinifera) in Afghanistan - Safdary, Ali Jawed; Ahamdi, Ahmad Jawid; Habibi, Nasratullah; Sadiq, Gul Agha (International Journal of Innovative Research and Scientific Studies, 2020)
This study was conducted to determine the chilling requirement of the Abjosh grape (local cultivar). The experiment was carried out based on randomized complete block design with three replications. The grape cuttings were treated at 5°C for (0, 100, 200, 250, 300, 350, 400, and 500 hrs) as chilling treatments at Samangan Higher Education Institute in the autumn of 2018. The traits such as the percentage of bud breaking, number of days to the first bud breakage, number of days to 50% of bud breaking, and number of days to the last bud breaking were measured. The results showed that the percentage of bud breaking increased significantly, as the chilling hrs (hours) increased. By the increasing of cold duration, the percentage of bud breaking in 500 hrs increased to 80% whereas, number of days to the first bud breaking, 50% of bud breaking and the number of days to the last bud breaking were decreased to 13, 14, and 16 days, respectively. Though, there were no significant differences between the 400 and 500 cold hrs in all indicators. The findings revealed that at least 300 hrs of cold duration is essential to reach an acceptable percentage of bud breaks, but further elaboration is needed.